Menyongsong Masa Depan UMKM: Strategi Manajemen Risiko Komprehensif untuk Mencapai Keunggulan Kompetitif - Abidin, Zainal (Maliki Interdisciplinary Journal, 2024)
This article raises the theme of risk management in Micro, Small and Medium Enterprises (MSMEs) with a focus on handling uncertainty and complex risks. In this context, the article explores the characteristics of MSMEs, the essence of risk and uncertainty, strategic decision making strategies in business management, as well as the types of risks that are the focus of MSMEs’ attention. The discussion extends to the specific risks that characterize the MSME business world, while providing a detailed view of risk management strategies adapted to ensure sustainable business continuity. Through a comprehensive exploration of these topics, this article concludes by providing comprehensive insight into how MSMEs can face uncertainty and manage risk efficiently to achieve long-term success and resilience in the face of dynamic market changes.